TELAAH PENERAPAN TRI-N (NITENI, NIROKKE, NAMBAHI) PADA BUKU BAHASA INDONESIA KELAS IX SMP - Siwi Damayanti; Siti Rochmiyati (Jurnal Muara Pendidikan, 2019)
The objective of the research is to know the application of process (1) niteni, (2) nirokke, and (3) nambahi on the student textbook Bahasa Indonesia Kelas IX SMP Kurikulum 2013. Niteni is give a mark and pay attention carefully using all sense with the process. Observing use vision sense, hearing sense, smelling sense, touching sence, dig the information more deeper from the result of the observation and reasoning with connecting the knowledge that already owned from the result of excavation. Nirokke is repcating what is already taught by the model/ example/from teacher/ the source study with involve, thinking, sensing, feeling/ conscience and spiritual with integral and hormontous with the process: repeating with writing, repeating with movement, repeating with experiment, repeating with demonstratiang/ practicing, repeating with rerving. Nambahi is and ing reducing what is already taught by the model/ example from the teacher/ the source sudy with developing creativity and idea with the process adding with desarning, adding with creating/ making, and adding with improvitation. The research is descriptive qualitative research the data of the research is word, phrase, sentence, paragraph and discourse that the contain is about the application of process niteni, nirokke, nambahi. Te result of the research shows that the application of the process niteni, nirokke, and nambahi already on the textbook.